Northern Asian Pliocene–Pleistocene beremendiin shrews (Mammalia, Lipotyphla, Soricidae): a description of material from Russia (Siberia), Kazakhstan, and Mongolia and the paleobiology of Beremendia. (November 2019) - Zazhigin, Vladimir S.; Voyta, Leonid L.
Abstract: Beremendiini is an extinct group of soricine shrews that were widely distributed during the Pliocene and Pleistocene. Their occurrence in China has been investigated, but their presence in northern Asian regions has remained poorly studied. This paper analyzes 56 fossil remains of Beremendiini collected from 16 early Pliocene to early Pleistocene localities in Russia (Siberia), Kazakhstan, and Mongolia and shows the presence of two beremendiin species: Beremendia fissidens (Petényi, 1864) and Beremendia minor Rzebik-Kowalska, 1976. Northern Asian Beremendia considerably vary in size and qualitative characteristics, although most of the different states have been identified in European or Chinese specimens. Through the application of geometric morphometric techniques, mandibular shape analyses reveal similarities between the members of the beremendiin genera Peisorex Kowalski and Li, 1963, Beremendia Kormos, 1934, and Lunanosorex Jin and Kawamura, 1996. Shape analyses and comparisons of mandibular characteristics reveal 'trophic' analogies between Beremendia and Blarina spp. and a new model of 'Mandible Swinging and Sliding' (MSS-model) accounting for the similarities in mandibular morphology with implications for the understanding of the diet of Beremendia . UUID:http://zoobank.org/ef92ee1a-3977-44b2-86d7-381665bcf78b